Sensory Quality and Antixidant Activity of Starfruit Syrup with the Addition of Roselle - Saputra, Harmoko; Dase Hunaifi; Yane Regiana; Feri Kusnandar (Program Studi Teknik Kimia, Universitas Pamulang, 2024)
Starfruit (Averrhoa bilimbi L.) and roselle flower (Hibiscus sabdariffa L.) possess the potential to be processed into syrup, enhancing its added value. This study determined best syrup formulation derived from a mixture of starfruit and roselle flower extracts, focusing on chemical attributes, sensory quality, and antioxidant capacity (IC50). Three formulations (F1, F2, and F3) comprising a mix of starfruit wuluh extract (ranging from 50-70%) and roselle flower extract (between 29.6-39.6%), added with 0.3% stevia and 0.1% xanthan gum, were prepared, pasteurized, and sealed in glass bottles. Changes in the antioxidant capacity of the selected syrup were monitored over a 5-week storage period. The combination of 50.0% starfruit extract with 49.6% roselle extract (F1) was prefered in terms of sensory quality (including color, taste, aroma, thickness, and overall acceptance) and its antioxidant attributes. The IC50 antioxidant activity of this syrup formulation exhibited a gradual decline over the 5-week storage duration.